Biosafety in Dental Health Care During the COVID-19 Pandemic: A Longitudinal Study - Lucyene Miguita; Roberta Rayra Martins-Chaves; Victor Emmanuel Viana Geddes; Suellen da Rocha Mendes; Sara Ferreira dos Santos Costa; Paula Luize Camargos Fonseca; Diego Menezes; Rafael Marques de Souza; Daniel Costa Queiroz; Hugo José Alves; Raphaela Alvarenga Braga de Freitas; Aline Fernanda Cruz; et al. (Frontiers Media S.A., 2022)
BackgroundThe coronavirus disease 2019 (COVID-19) pandemic had quite an impact on dental health care. Concerns about the risk of SARS-CoV-2 transmission through contaminant fluids and droplet formation during several dental procedures highly impacted dental health care, drastically reducing the number of dental practices worldwide. To monitor SARS-CoV-2 contamination in dental clinics, a longitudinal study was carried out during the return of dental practice at university.MethodsDental health care professionals [(DHCPs); teachers, undergraduate dental students, and dental assistants] and patients were screened for SARS-CoV-2 RNA in a dental school clinic environment from 11th January to 12th March 2021 (9 weeks). Serological testing was performed on DHCPs in two-time points. Additionally, samples with low Ct values were sequenced to identify the circulating SARS-CoV-2 variant and possible transmission clusters.ResultsWe found a low number of dental staff (5.8%), patients (0.9%), and environment sites (0.8%) positive for SARS-CoV-2. Most positive cases had asymptomatic to mild symptoms, and two asymptomatic DHCPs presented prolonged infection. In the first week after previous exposure to COVID-19, 16.2% of DHCPs had IgM or IgG antibodies against SARS-CoV-2, and 1/3 of them had undetected antibodies in the last weeks. The variant zeta (P.2) could be detected. No cross-infection was observed between participants.ConclusionOur study suggests that dental practice can be safely executed when adequate control measures and biosafety protocols are applied. DHCP and patient testing, patient telemonitoring, proper use of personal protection equipment, and sanitization of surfaces are essential to avoid SARS-CoV-2 cross-infection in dental practice.